Fitting of anisotropic strength parameters of laminated shale and its influence on wellbore instability - Jinyou Zhang; Xiaobo Liu; Hongge Jia; Xuejia Du; Zhongmin Wang; Guoqiang Pan; Mingming Zhang (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract To understand the intrinsic causes and influencing factors of shale wellbore instability, the anisotropic mechanical properties of layered rocks is analyzed. Using the existing strength test data of shale with different bedding angles, the variation characteristics of rock strength with bedding are investigated, and the prediction accuracy of different types of anisotropic strength criteria are validated by using the experimental data. Then, based on the thermal-hydro-mechanical stress model of the cemented wellbore, combined with the selected anisotropic strength criteria, we conducted a systematic study on the variation law of wellbore collapse pressure in shale formations. The results show that the Pariseau criterion can distinguish the strength difference between vertical and horizontal bedding, but the prediction error is large. In contrast, the single plane of weakness model (SPW) and patchy plane of weakness model (PPW) criteria cannot distinguish the strength difference between vertical and horizontal bedding but have better predictive performance for the strength during shear slip failure along the bedding plane. Additionally, the PPW criterion has higher prediction accuracy for rock strength than the SPW criterion within the bedding angle ranges of 0 ~ β1 and β2 ~ 90°. The collapse pressure contour maps predicted by the SPW and PPW criteria are similar, while those predicted by the Pariseau criterion show significant differences, with the Pariseau criterion underestimating the wellbore collapse pressure in shale formations, potentially leading to severe consequences. The predictions of the PPW and SPW criteria are safer and more reliable. In the studied layered shale formations, when the well deviation angle is less than 60°, drilling along the up-dip direction provides better wellbore stability; when the well deviation angle is greater than 60°, drilling along the down-dip direction provides better wellbore stability. Additionally, under any bedding orientation condition, the collapse pressure of a horizontal well is higher than that of a vertical well, but the collapse pressure of a vertical well is more sensitive to changes in bedding orientation, with greater fluctuation range. These research findings provide a scientific basis for the design and construction schemes of drilling engineering, ensuring the safety and efficiency of drilling operations.